Push and pull - Schaefer, Lola M. (Mankato, Minnesota : Capstone Press, 2000)
Simple text and photographs illustrate push and pull movement
Includes bibliographical references and index.
Keywords: Mechanics -- Juvenile literature; Force and energy -- Juvenile literature